2005
DOI: 10.1517/14796694.1.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Scene Investigation: How a Cold Virus Became a Tumor Killer

Abstract: Oncolytic therapy is a novel anticancer treatment with attenuated lytic viruses such as adenovirus (Ad). These viruses kill the host cells through their lytic replication cycle and are thus distinct from classical gene therapy viruses, which serve as gene delivery agents and do not replicate. Oncolytic Ads are genetically engineered so as to replicate only in cancer cells. Their replication cycle leads to viral multiplication, the killing of the host cells and spreading of the infection throughout the tumor. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The replicative capacity of HYPR-Ad-IL4 in vitro was attenuated 10-to 100-fold compared with dl309-Ad depending on the cell line tested ( Table 1). The reasons for this are currently unknown but may in part relate to differences in the E3 gene region between the two viruses (11). Despite this, HYPR-Ad-IL4 was able to effectively induce cytolysis in vitro, and most importantly, its in vivo antitumor activity was equivalent to dl309-Ad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replicative capacity of HYPR-Ad-IL4 in vitro was attenuated 10-to 100-fold compared with dl309-Ad depending on the cell line tested ( Table 1). The reasons for this are currently unknown but may in part relate to differences in the E3 gene region between the two viruses (11). Despite this, HYPR-Ad-IL4 was able to effectively induce cytolysis in vitro, and most importantly, its in vivo antitumor activity was equivalent to dl309-Ad.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying principle for this developing cancer therapy is that the virus will selectively replicate in tumor cells, resulting in an exponential increase of the virus inoculum and the establishment of repeating cycles of cell infection, virus replication, and tumor cell death. Treatment of cancer patients with oncolytic Ads in clinical trials has shown the overall safety of this therapy and modest antitumor activity (11). The differential activation of HIF/HRE-dependent gene expression in tumors compared with normal tissue provides an opportunity for the design of a targeted oncolytic Ad that would depend on HIF expression for its replication.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer therapy by means of oncolytic viruses has attracted attention of clinicians, wet lab oncologists and mathematical modelers (Bell, 2007; Bell et al, 2003; Crompton and Kirn, 2007; Davis and Fang, 2005; Kaplan, 2005; Kelly and Russell, 2007; Kirn and McCormick, 1996; McCormick, 2003; McCormick, 2005; Novozhilov et al, 2006; O'Shea, 2005; Parato et al, 2005; Post et al, 2005; Roberts et al, 2006; Vaha-Koskela et al, 2007; Wodarz, 2001; Wodarz, 2003). The idea behind this treatment is to infect a tumor with engineered viruses which specifically infect and kill tumor cells, and have the potential to spread throughout the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of TS blocks dTTP production and prevents DNA synthesis 5-7 . The CD/5FC system has been used in numerous animal models 8-10 and is currently being evaluated in clinical trials for solid tumors [11][12][13][14][15] . One limitation to this approach is the poor transfection efficiency of current vector delivery systems.…”
Section: Introductionmentioning
confidence: 99%